Local Government Responsibility for Home Care Services at Primary Health Care - Katmini Katmini; Tauchid Noor; Mohammad Zamroni (GLOBAL HEALTH SCIENCE GROUP, 2024)
Health has a major role in improving the degree of community life, therefore all countries strive to organize the best possible health services. The purpose of the study was to analyze the responsibility of local governments for home care services at primary health care center. This research uses normative legal research methods with a conceptual approach. Reference primary legal materials and secondary legal materials. The article was retrieved from a scientific journal databaseThe development of home care among the community is better if balanced with the quality of service. Apart from various obstacles in its implementation, the existence of home care is very important for today's society. Because the fundamental problem that is often experienced is the number of referrals to clinics from the local area that require clinical care. Before the existence of home care, individuals with health complaints needed to meet face-to-face at hospitals, polyclinics, and other welfare administration units. After home care was established, individuals who wanted to initiate medical services could simply call the hotline provided, making it more useful for the local area to gain access to healthcare. It is believed that home care will be the first stage of administrative data collection before referral to hospitals and clinics.